Germany's role in the foreign direct investment configuration of Korean multinational enterprises in Europe - Chan-Mi Strüber (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2009)
Germany has always been one of the major direct investment destinations for Korean multinational enterprises (MNEs) within Europe. However, along with the internationalization of Korean firms, the motives and patterns for direct investments have changed. This paper discusses the development of Korean MNEs' investment motives and patterns, specifically regarding the role Germany has played over the years. For this purpose, geographical configuration patterns of the largest Korean MNEs within Europe are analyzed. The main findings indicate that Germany is considered more important to automobile companies than electronics companies, and that the investment activities of small and mediumsized enterprises are increasing, whereas the investment activities of large MNEs are decreasing.
Keywords: 330; foreign direct investment; geographical configuration; multinational enterprises; internationalization; Korea; Germany; Europe; Direktinvestition; Multinationales Unternehmen; Südkoreanisch; Südkorea; Deutschland; Europa